Legalitas Pernikahan Siri di Indonesia - Rahajaan, Jacobus Anakletus (Public Policy, 2020)
Abstract This study aims to analyze the legality issues of siri marriages which have become polemic in the life of the people in Indonesia and their impact on women and children according to Indonesian marriage law, which is regulated according to Law Number 1 of 1974 concerning marriage. This study uses the type or type of Normative Legal research and library research, using the statutory approach, conceptual approach, and the comparative approach. This study uses these approaches because what is examined here is the rule of law and/or legislation relating to marital marriages. The research results are then analyzed and described qualitatively. The results of this study indicate that, Law Number 1 of 1974 concerning marriages is still ambiguous, there is a norm conflict between one article and another that causes confusion and differences in perception among the community that triggers polemics. So that through the results of normative juridical studies, this research concluded that based on legal principles and legal norms in Law No. 1 of 1974 concerning marriages along with other statutory regulations, Siri marriages are marriages that are considered illegal. Thus, this legal juridical illegitimate marriage will have a very detrimental effect on the parties, especially women and children who are bound in the marital relationship of Siri. Keywords: Legality, Siri Marriage